35th Australian and New Zealand Society for Neuropathology (ANZSNP) Scientific Meeting - Meeting Abstracts, August 31st - September 1st, 2024 - The Australian and New Zealand Society for Neuropathology (ANZSNP) (Free Neuropathology)
The ANZSNP scientific meeting 2024 was held in the scenic city of Queenstown, New Zealand on 31 August and September 1. Dr Fouzia Ziad, President of the ANZSNP and Dr Laveniya Satgunaseelan, Secretary /Treasurer of the ANZSNP were the convenors of the meeting. The meeting was co-badged with the Australasian Winter Conference on Brain Research (AWCBR) 2024. There were 55 registrants from Australia, New Zealand, USA, Europe and Asia.